Application of intelligent systems in multi-modal information analytics : proceedings of the 2020 International Conference on Multi-model Information Analytics (MMIA2020).: proceedings of the 2020 International Conference on Multi-model Information Analytics (MMIA2020). Volume 2 ([2021]) - Unknown
No abstract available